2016
DOI: 10.1002/adsp.12017
|View full text |Cite
|
Sign up to set email alerts
|

Using Geriatric Standardized Patients and Technology to Teach Counseling and Health Science Students How to Work Interprofessionally

Abstract: The need for health care providers with geriatric-specific training in the United States is growing. This qualitative article focuses on the reflections of interprofessional health and behavioral science students' involvement participating in a unique 1-day standardized patient experience. Results indicated the experience was positive and meaningful for students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Training should focus on engaging in low-risk IP opportunities such as simulated IP education experiences, cited in the literature as helpful for assisting in developing IP competencies (Johnson et al, 2015). Connecting with local universities or with distance technologies online accomplishes this (Fowler & Hoquee, 2016). Understanding interprofessionalism and the differences between collaboration and consultation, which is often a confusion noted in the literature (Johnson & Mahan, 2019; Kemer et al, 2019), is important to engage with opportunities for professional development and continuing education.…”
Section: Implications and Recommendations For Rural Mental Health Promentioning
confidence: 99%
“…Training should focus on engaging in low-risk IP opportunities such as simulated IP education experiences, cited in the literature as helpful for assisting in developing IP competencies (Johnson et al, 2015). Connecting with local universities or with distance technologies online accomplishes this (Fowler & Hoquee, 2016). Understanding interprofessionalism and the differences between collaboration and consultation, which is often a confusion noted in the literature (Johnson & Mahan, 2019; Kemer et al, 2019), is important to engage with opportunities for professional development and continuing education.…”
Section: Implications and Recommendations For Rural Mental Health Promentioning
confidence: 99%
“…These interventions can take the form of seminars, 16-week courses, conferences, or brief time-limited interventions (Olson & Bialocerkowski, 2014) . These opportunities typically engage students in content related to interprofessional collaboration competencies for engagement (Johnson & Freeman, 2014) and/or specific themes that require interprofessional collaboration, such as geriatric care (Fowler & Hoquee, 2016) . Through the various types of IPE interventions, research has found improvement in multiple areas of career development and professional identity (Johnson & Mahan, 2019;Martinussen et al ., 2012) .…”
Section: Interprofessional Engagement Interventionmentioning
confidence: 99%
“…IPE training in professional health care settings, such as communications courses or team effectiveness interventions, has shown promise with increasing career self-efficacy-belief that one can perform career-related tasks-amongst doctors, nurses, nursing assistants, and other allied health professionals (Buljac-Samardzic et al ., 2010;Nørgaard et al ., 2012) . In allied health professions, IPE is a promising intervention to enhance career development and self-efficacy, and there is some preliminary evidence that it could be beneficial for counselor trainees (Fowler & Hoquee, 2016;Johnson et al ., 2015) . The results of a study investigating the effectiveness of an interprofessional geriatric course that included counselor trainees indicated that counselors' readiness as it relates to working from an interprofessional framework in geriatrics was higher after a 16-week interprofessional course (Fowler & Hoquee, 2016) .…”
Section: Career Development and Ipementioning
confidence: 99%
See 1 more Smart Citation
“…The counseling profession has established a need for research and best practices for counseling older adults because of its emphasis on development across the life span (Kampfe, 2015;Myers & Harper, 2004), student and professional interest in gerontology (Foster et al, 2009(Foster et al, , 2014Fowler & Hoquee, 2016;Wagner et al, 2019), and legislative advocacy opportunities (Bergman, 2013). With Medicare reimbursement for counselors as a primary focus of legislative advocacy efforts (Field, 2017;Fullen, 2016), there is a need to legitimize gerontological counseling (GC) as a credible area of competency for counseling professionals, both as an avenue for improving client care across the life span and as proof that the counseling profession possesses relevant educational and training competencies to substantiate inclusion of counselors as Medicare-eligible providers (Bergman, 2013).…”
mentioning
confidence: 99%